FUNCTIONS OF REMUNERATION IN THE PUBLIC SECTOR AS AN ACCOUNTING CATEGORY - Khrystyna Kydysiuk (State and Regions. Series: Economics and Business, 2026)
The article examines the functions of remuneration in the public sector as an accounting category, taking into account its economic essence and the specific features of its functioning as an object of accounting in public sector institutions. The study substantiates the need to expand traditional approaches to defining the functions of remuneration by integrating economic, social, and accounting and managerial dimensions into its analysis. An analysis of scholarly approaches to the functions of wages and accounting has revealed the absence of a unified classification framework and has justified the expediency of distinguishing the functions of remuneration from the perspective of the subject area of accounting in public sector institutions. The study proposes a systematisation of remuneration functions into two interrelated groups: economic and social functions, and accounting and managerial functions. The first group includes reproductive, social, incentive (motivational), regulatory, and distributive functions, which reflect the role of remuneration within the system of social and labour relations. The second group comprises informational, control, managerial, and analytical functions, as well as the functions of ensuring transparency and accountability and ensuring compliance, which characterise remuneration as an independent object of accounting in public sector institutions. It is demonstrated that the proposed approach provides a comprehensive understanding of the role of remuneration in public financial management, internal control, public sector auditing, and the transparent and efficient use of budgetary resources. The classification of payroll functions into distinct groups facilitates meeting the information needs of users in the context of reforms to the remuneration system in public sector institutions. The proposed classification of remuneration functions contributes to the further development of the theoretical foundations of remuneration accounting in the public sector and enhances the information support of managerial and control processes within public sector institutions.